Three cases of localized cutaneous nodular amyloidosis in patients with limited systemic sclerosis and a brief literature review - L.S. Goettsche, BS; M.S. Moye, MD; A.J. Tschetter, MD; M.S. Stone, MD; K.A. Wanat, MD (Wolters Kluwer, 2017)
Localized cutaneous nodular amyloidosis (LCNA) is the rarest form of localized cutaneous amyloidosis. In patients with LCNA, local plasma cells secrete immunoglobulin light chains called amyloid L via an unknown mechanism. LCNA has been associated with autoimmune connective tissue diseases such as most commonly Sjögren syndrome. A few reported cases of LCNA are associated with limited systemic sclerosis (LSSc). We report three cases of LCNA in patients with LSSc to add to the existing literature, discuss the disease association and proposed pathophysiology, and briefly review the existing information in current literature. It is important to closely follow patients with LCNA to monitor progression to systemic amyloidosis. Keywords: nodular amyloidosis, limited systemic sclerosis, connective tissue disease, histopathology